ESCALATION OF TENSION IN KYRGYZ-TAJIK RELATIONS IN 2015-2022: FULL-SCALE ARMED CONFLICTS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article talks about the fact that the Kyrgyz-Tajik border, 970 km long, is one of the most difficult in the region, due to the mountainous landscape and the presence of the Tajik enclave of Vorukh in Kyrgyzstan. Only in 2015 did the Kyrgyz Republic and Tajikistan reach agreement on the 520 km border.Recently, the already difficult situation in the border zone has sharply worsened regarding disputed areas, distribution of water resources, and strict border control. In 2020 alone, there were more than a dozen armed clashes between border communities of the two countries. The largest armed conflicts involving army units and the use of military equipment occurred in April 2021 and September 2022. These were the largest conflicts between the Kyrgyz Republic and the Republic of Tajikistan in the post-Soviet period.The article emphasizes that in order to resolve differences, both sides need to compromise. But first of all, it is necessary to resolve the problems with the disputed areas and complete the internaional legal registration of borders.
Keywords: Kyrgyz-Tajik border, border zone, disputed territories, Vorukh enclave, tension, armed conflicts, settlement